Periósteo como opção de tratamento das perfurações da membrana sinusal em procedimentos de levantamento do soalho do seio maxilar - Oliveira, Hany Angelis Abadia Borges de (2013)
Maxillary sinus lifting is a technique to increase bone volume in atrophic maxilla, with autogenous bone and/or biomaterials, in order to place implant. This procedure may lead to some complications such as bleeding, maxillary sinus infection, wound dehiscence, sinus fistulae, chronic sinusitis, and loss of the graft. Most of these complications can be related to perforation of the sinus membrane, that occurring in 10 to 35%, which undertakes the use of particulate grafts. Different techniques are proposed to obliterate the sinusal perforation, such as folding or suturing membrane, use of a cyanoacrylate adhesive, fibrin glue, plasma rich in growth factors, collagen membrane, conjunctive graft. The resorbable collagen membranes have been the most common option to treat a sinus membrane perforation. This biomaterial operates as a mechanical barrier that prevents the invasion of connective and epithelial tissues inside the bone cavity. Whereas the periosteum is a membrane collagen, it could be used for treating sinus membrane perforation. The present study proposes to evaluate the clinical effectiveness of the autogenous periosteum, used for obliteration of sinus membrane perforation occurred in procedures maxillary sinus lifting. From January 2009 to November 2012 were selected 81 procedures maxillary sinuses lifting in healthy subjects ranging from 25 to 60 years of age. In these, there were 16 procedures with sinus membrane perforations. The study group was divided into 2 subgroups: subgroup I - patients whose sinus membrane was perforated and obliterated with periosteum graft and subgroup II- patients whose membrane was not perforated. Those who had the sinus membrane perforation were treated with autologous periosteum removed from the bone graft donor region, retromolar area. Patients were followed daily for the first 10 days until the sutures were removed and monitored every two weeks two month. All patients tolerated the procedure using the periosteum as a treatment for a sinus membrane perforation during sinus lifting and their post-surgical results were uneventful. During the post-operation period was observed only a slight swelling at the graft donor site. The clinical and radiographic follow-ups of patients after surgery demonstrated that the proposed technique is clinical effective, and the periosteum can be used in the various sizes of perforations, since that the membrane is not completely dilacerated. Whereas with the viability of the procedure and the clinical results, it is possible to conclude that periosteum is effective in treatment of sinus membrane perforation.